2018
DOI: 10.1080/15384101.2017.1403688
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA LOC100507600 functions as a competitive endogenous RNA to regulate BMI1 expression by sponging miR128-1-3p in Hirschsprung's disease

Abstract: Recently studies reported that long non-coding RNAs (lncRNAs) may take part in a lot of congenital diseases, meanwhile, Hirschsprung's disease (HSCR) is a major congenital digestive tract malformation. Nevertheless whether lncRNAs participate in the occurrence of HSCR and how it contributes to this disease are still unknown. LOC100507600 was selected from our gene expression microarray data obtained from bowel tissues from HSCR patients and negative controls. Subsequently, we used qRT-PCR to prove the result i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…In the cytoplasm, lncRNAs can bind to target mRNAs to affect their translation or mediate their stability [23]. In addition, lncRNAs may act in the cytoplasm as competing endogenous RNAs (ceRNAs) [24,25]. In this study, H19 was mainly distributed in the cytoplasm of endometrial cancer, and we speculate that it functions as a ceRNA.…”
Section: Discussionmentioning
confidence: 70%
“…In the cytoplasm, lncRNAs can bind to target mRNAs to affect their translation or mediate their stability [23]. In addition, lncRNAs may act in the cytoplasm as competing endogenous RNAs (ceRNAs) [24,25]. In this study, H19 was mainly distributed in the cytoplasm of endometrial cancer, and we speculate that it functions as a ceRNA.…”
Section: Discussionmentioning
confidence: 70%
“…It has been confirmed that some protein coding genes participate in the pathogenesis of HSCR, including RET, EDNRB, PHOX2B, SOX10, etc [3,4]. To date, some noncoding RNAs have also been proven to take part in the biological processes of HSCR, such as microRNA-939, lncRNA HOTTIP and LOC100507600 [5][6][7]. However, the underlying pathogenesis of HSCR occurrence still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Much evidence suggests a relationship between lncRNAs and HSCR, all based on the comparative expression assays of specific lncRNAs in bowel tissue from HSCR patients and controls [73][74][75][76][77][78]. In our study we have performed a differential qRT-PCR assay in the EPCs from HSCR patients and controls, which has allowed us to identify new lncRNAs as potential regulatory elements implicated in ENS development and HSCR onset.…”
Section: Discussionmentioning
confidence: 99%